Improving The Physical Properties of Young Teak Wood Through Phenol Formaldehyde Compregnation - Agung Dwi Saputra; Joko Sulistyo (Wood Research Journal, 2021)
Young teak wood exhibits inferior properties due to a high proportion of juvenile wood and sapwood. The modification through compregnation of phenol formaldehyde is required to improve wood qualities. Therefore, this study aimed to observe the possibility of improving the physical properties of young teak wood (15 years) using phenol formaldehyde compregnation at various concentrations (5%, 10%, 15%) and pressing times (15, 30, 60 minutes). The results showed that phenol formaldehyde concentration produced retention with a maximum value of 31.19 kg/m3. Based on wood without treatment (controls), the compregnation significantly increased the redness (a*) level by 45.57% and the specific gravity by 7.93%. The decreasing levels after treatment were observed in the brightness (L*) (by 36.56%), the yellowness (b*) (by 38.40%), and air-dried moisture contents by (by 5.44%). Furthermore, the reduction in hygroscopicity was observed in an equilibrium moisture content level in various relative humidity, as well as in increasing the stability dimension, though in a small magnitude.